MOR2 ecological data - Reid, R. S.; Jamsranjav, C.; Fernández-Giménez, M. E.; Laituri, M.; Jamiyansharav, Kh.; Altanzul, T.; Baasandorj, Ya.; Zumberelmaa, D. (Colorado State University. Libraries, 2020)
MOR2 ecological data were collected from 143 winter camps at three different grazing distances in four different ecological zones. Ecological field data includes soil pit descriptions, soul surface data including resource retention class and soil redistribution class data; site environmental data (i.e. metadata), and vegetation data including plant biomass by functional group and plant cover by species.
Those listed as authors substantially designed instruments and data collection protocols, directly supervised data collection and collected data, designed database, and oversaw data entry and quality checking.
Additional acknowledgements (People listed assisted with field data collection, data entry, and establishment of on-line data archive): The following individuals helped with data collection or data entry and consulting: Adyabadam G., Ariunsukh, Ariunzaya, Arren A., Atarbold, Baagii, Bolormaa, Batkhishig B., Bayarmaa B., Brandon B., Bulgamaa, Bulgana U., Byambaa, D., Dejidmaa Ts., Erica C., Enkhjargal, Enkmunkh B., Gandiimaa, Ganjargal, Gankhuyag L., Gantsogt, Itgelt N., Jargal Ya., Jay A., Justin V., Khishigdorj, Khishigjargal B., Lkhagvasuren D., Lkhagvasuren, Lkhamdulam, Narangerel, Naransogt, Niah V., Odgarav J., Oyuntsetseg, Oyunsuvd S., Pagmajav D., Retta B., Sainchuluun A., Sergelen M., Solongo, Sophia L., Sukhbaatar, Sumjidmaa, Tsengelmaa L., Tserendash S., Tsogtbaatar J., Tumee, Turbagana, Undarmaa J., Unurzul A., Urlee, Vandandorj S., Zolzaya, other members of our great field teams, local government officers and supporters. The following individuals guided establishment of on-line data archive at Colorado State University: Tobin Magle, Mara Sedlins, Daniel Draper
The following institutions helped and participated in the project: Nutag Action Research Institute, Institute of Geo-Ecology, Research Institute of Animal Husbandry, Mongolian Society for Range Management, German Technical Cooperation (GTZ) , Institute of Botany, Institute of Meteorology and Hydrology, Institute of Chemistry and Chemical Technology, Mongolian State Agricultural University, Center for Ecosystem Studies, Texas A&M University and Colorado State University.
Warner College of Natural Resources
Keywords: Mongolia; ecology; plant species; soil